Europejski system nagród EFQM na przykładzie Volkswagen Motor Polska z Polkowic - Bobik, Dorota (EFQM European Award System on the example of Volkswagen Motor Poland from Polkowice, 2008)
The classical approach to the EFQM Excellence Award (EEA) assessments, which requires the preparation of a 75-page submission document, is seen by a growing number of potential applicants as an obstacle to enter the award process. EFQM exchanged views with all stakeholders of this process: applicants, assessors, jury members, the award office and GEM – Global Excellence Model council and prepared a new approach, so called 2005+. The new approach was put into practice for the first time in 2005. Volkswagen Motor Polska from Polkowice was the first company in Poland that applied on the basis of the new method 2005+. In 2007 VWMP reached the final of EEA.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 151-164